If $a+\sqrt{a}=b+\sqrt{b}$, does this automatically mean that $a=b$?

I first tried to square both sides but that seemed to get me nowhere.


Can we just conclude that $a$ has to be equal to $b$ to make this expression to be true?

  • 6
    $\begingroup$ Hint: what is the derivative of $f(x) = x+x^{1/2}$? $\endgroup$
    – Integrand
    Aug 21 '20 at 22:42
  • $\begingroup$ @Integrand ohhh $\endgroup$
    – John Rawls
    Aug 21 '20 at 22:45

If $a>b$ then $ \sqrt{a}>\sqrt{b}$ and $LHS>RHS$. If $a<b$ then $LHS<RHS$. Thus $a=b$.


Let $a\ge 0$ and $ b\ge 0 $ such that $$a+\sqrt{a}=b+\sqrt{b}$$ then

$$a-b=\sqrt{b}-\sqrt{a}$$ $$=(\sqrt{a}+\sqrt{b})(\sqrt{a}-\sqrt{b})$$



but $$\sqrt{a}+\sqrt{b}+1\ne 0$$

thus, necessarily $$\sqrt{a}=\sqrt{b}$$ and $$a=b$$


$a-b=\sqrt{a}-\sqrt{b} \implies (\sqrt{a}-\sqrt{b})(-1+\sqrt{a}+\sqrt{b})=0\implies \sqrt{a}=\sqrt{b}$ or $1=\sqrt{a}+\sqrt{b}$. So it might not be the case that $a = b$.

I realize my answer above is for a different problem. So back to this one. We have $a - b = \sqrt{b} - \sqrt{a} \implies a - b +\sqrt{a}-\sqrt{b} = 0 \implies (\sqrt{a}-\sqrt{b})(1+\sqrt{a}+\sqrt{b}) = 0 \implies \sqrt{a} = \sqrt{b} \implies a = b$ .


Let $f(x) = x + \sqrt x$. Then, we have $f'(x) = 1 + 1/(2\sqrt x) > 0 ~ (\forall x>0)$. Therefore, $f(x)$ is strictly increasing and $f(a) = f(b) \implies a = b$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.